Effectiveness of nutritional counseling and fe tablet supplementation on hemoglobin levels of pregnant women in the working area of the Hajimena Health Center, Lampung - Nur Wachiniah Mawadda; Harny Citra Purnama; Nurul Amalia; Qorinah Estiningtyas Sakilah Adnani; Chyntia Haryana (Science Midwifery, 2026)
Pregnancy-related anemia remains a significant public health problem in the working area of Puskesmas Hajimena, Natar Subdistrict, South Lampung, increasing the risk of preterm birth and low birth weight. Although iron (Fe) supplementation is routinely provided through antenatal care (ANC), anemia remains prevalent, suggesting that supplementation alone may be insufficient to address nutritional and behavioral factors affecting maternal hemoglobin (Hb) levels. This study addressed limited evidence regarding the integration of Health Belief Model (HBM)-based nutrition counseling with Fe supplementation in primary healthcare settings. A quasi-experimental pretest-posttest study with a control group involved 98 second-trimester pregnant women equally allocated into intervention and control groups. The intervention group received three HBM-based nutrition counseling sessions over eight weeks alongside Fe tablets, while the control group received Fe tablets alone. The intervention significantly increased Hb levels and reduced anemia prevalence. The novelty lies in integrating behavioral-based nutrition counseling into anemia prevention. Scientifically, the findings provide evidence that behavioral interventions can enhance Fe supplementation effectiveness. Practically and clinically, the intervention offers a feasible strategy for midwives to improve maternal knowledge, adherence, dietary practices, and anemia management within ANC services. From a policy perspective, the findings support integrating structured nutrition counseling into routine maternal health programs to strengthen anemia prevention and improve maternal health outcomes.